Perspectives on High Real Interest Rates in Turkey - Kannan, Prakash (IMF Working Papers; Working Paper, 2008)
The Turkish economy is typically characterized as having particularly high real interest rates. Fundamental considerations, such as high growth rates or high returns to capital, do not provide a satisfactory resolution of this puzzle. Instead, we find that two other factors- doubts about the sustainability of disinflation and the existence of a risk premium-have a significant impact on the level of real interest rates in Turkey. Importantly, fiscal policy variables are shown to affect both these factors, suggesting that a more credible and prudent fiscal policy can help reduce real interest rates in Turkey.